ALEXANDER PAYNE’S NEBRASKA AND THE RETURN OF THE GRAND NARRATIVES - Bolaño Quintero, Jesús (Revista Internacional de Culturas y Literaturas, 2019)
This article analyses Alexander Payne’s film Nebraska from the perspective of the paradigm shift produced after the much-debated passing of postmodernism, announced by theorists such as Ihab Hassanor Linda Hutcheon. We shall examine how the lack of grand narratives makes it almost impossible to give structured meanings to the concept of reality. Payne’s project can beviewed as both an allegorical and a physical journey that takes the character to no specific destination in his search to make amends with the harsh reality that, ultimately, spells the end of the American Dream.